2014
DOI: 10.7314/apjcp.2014.15.21.9225
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Capecitabine Treatment and Contributing Factors among Cancer Patients in Malaysia

Abstract: Ensuring adherence to chemotherapy is important to prevent disease progression, prolong survival and sustain good quality of life. Capecitabine is a complex chemotherapeutic agent with many side effects that might affect patient adherence to treatment. This cross sectional study aimed to determine adherence to capecitabine and its contributing factors among cancer outpatients in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
2
16
2
Order By: Relevance
“…Diarrhea is a specific severe side effect commonly reported by patients taking capecitabine. 4 Findings from our study confirmed the impact of the severity of diarrhea on capecitabine adherence rates, 14 although the average rate of the severity of diarrhea at 6 weeks was not high. We did find that patients who ever rated their experience with diarrhea as severe or very severe during 6 six weeks had significantly higher adherence rates.…”
Section: Effectiveness Of Self-managementsupporting
confidence: 70%
See 2 more Smart Citations
“…Diarrhea is a specific severe side effect commonly reported by patients taking capecitabine. 4 Findings from our study confirmed the impact of the severity of diarrhea on capecitabine adherence rates, 14 although the average rate of the severity of diarrhea at 6 weeks was not high. We did find that patients who ever rated their experience with diarrhea as severe or very severe during 6 six weeks had significantly higher adherence rates.…”
Section: Effectiveness Of Self-managementsupporting
confidence: 70%
“…We found the positive direction of potential associations between adherence rates and the severity of side effects, which was in the opposite direction of what has been reported in the literature. 14 There are several possible reasons for this. For example, people who take their full dose of capecitabine may experience more side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer patients are often thought to be highly motivated by the gravity of their disease, with “too much to lose” by being nonadherent (Ziller et al 2009 ; Waterhouse et al 1993 ; Zahrina et al 2014 ; Winterhalder et al 2011 ). Recent studies reported adherence rates between 82.6 and 96.8 % in patients suffering from metastatic disease (Figueiredo Junior and Forones 2014 ; Smith et al 2015 ; Timmers et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a substantial number of studies in the past decades (DiMatteo 2004 ; Vermeire et al 2001 ) there is still no “gold-standard” method (Foulon et al 2011 ; Grymonpre et al 2006 ; Vermeire et al 2001 ; Banning 2008 , 2012 ; Waterhouse et al 1993 ; Escalada and Griffiths 2006 ) in measuring adherence and only a combination of measures can maximize accuracy (Osterberg and Blaschke 2005 ; Wang et al 2004 ; Zahrina et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%